Single-center experience using anakinra for steroid-refractory immune effector cell-associated neurotoxicity syndrome (ICANS). Issue 1 (7th January 2022) - Wehrli, Marc; Gallagher, Kathleen; Chen, Yi-Bin; Leick, Mark B; McAfee, Steven L; El-Jawahri, Areej R; DeFilipp, Zachariah; Horick, Nora; O'Donnell, Paul; Spitzer, Thomas; Dey, Bimal; Cook, Daniella; et al.
Abstract : In addition to remarkable antitumor activity, chimeric antigen receptor (CAR) T-cell therapy is associated with acute toxicities such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS). Current treatment guidelines for CRS and ICANS include use of tocilizumab, a monoclonal antibody that blocks the interleukin (IL)-6 receptor, and corticosteroids. In patients with refractory CRS, use of several other agents as third-line therapy (including siltuximab, ruxolitinib, anakinra, dasatinib, and cyclophosphamide) has been reported on an anecdotal basis. At our institution, anakinra has become the standard treatment for the management of steroid-refractory ICANS with or without CRS, based on recent animal data demonstrating the role of IL-1 in the pathogenesis of ICANS/CRS. Here, we retrospectively analyzed clinical and laboratory parameters, including serum cytokines, in 14 patients at our center treated with anakinra for steroid-refractory ICANS with or without CRS after standard treatment with tisagenlecleucel (Kymriah) or axicabtagene ciloleucel (Yescarta) CD19-targeting CAR T. We observed statistically significant and rapid reductions in fever, inflammatory cytokines, and biomarkers associated with ICANS/CRS after anakinra treatment. With three daily subcutaneous doses, anakinra did not have a clear, clinically dramatic effect on neurotoxicity, and its use did not result in rapid tapering of corticosteroids; although neutropenia and thrombocytopenia were common at the time of anakinra dosing, there were no clear delays in hematopoietic recovery or infections that were directly attributable to anakinra. Anakinra may be useful adjunct to steroids and tocilizumab in the management of CRS and/or steroid-refractory ICANs resulting from CAR T-cell therapies, but prospective studies are needed to determine its efficacy in these settings.